Pemanfaatan Teknologi Terhadap Peningkatkatkan Kualitas Pelayanan Posyandu Pada Puskesmas Tanah Toa Kecamatan Kajang Kabupaten Bulukumba - Malikul, Ahmad; Syam, Andi Armayudi; Sangirang, Andi Baso (Universitas Muhammadiyah Makassar, 2024)
Efforts to improve the quality of service are something that must be done by every agency, both public and private. Tanah Toa Health Center is an agency or institution that always strives to improve the quality of its services to get satisfaction for the people who use its services in the health sector. The use of technology is also pursued by Tanah Toa Health Center staff. Toa in improving the quality of its services, such as ensuring the quality of services provided to mothers and children at each posyandu handled by Tanah Toa health center officers. The aim of this research is to describe the use of technology to improve the quality of Posyandu services at the Tanah Toa Community Health Center, Kajang District, Bulukumba Regency. The methodology used in this research is qualitative research, namely research strategies and techniques used to understand the phenomena that occur by collecting as many in-depth facts as possible, the data is presented in verbal form, not in the form of numbers. The results of this research show that the services provided by Tanah Toa Community Health Center officers after utilizing technology in an effort to improve the quality of services, especially the services provided to mothers and children at each posyandu handled have shown good results, the first being measuring the height and weight of the baby, on inputting the height and weight measurement results, the data is immediately integrated and produces the ideal age for babies who have a certain height and weight and secondly it can confirm the routine of the mother and baby who carry out regular examinations (documentation and track records), The benefit is that community health center officers can find out in reel time about mothers and children who routinely check the health condition or growth of mothers and children. The conclusion of this article is that the use of technology in Posyandu handled by the Tanah Toa Community Health Center which consists of 23 posyandu located in 5 villages has shown a positive impact in increasing efficiency and quality of service, so that mothers and children can be assured of getting good health services.